Construction of the elements based on lifted multiwavelet and its applications. Issue 172 (12th June 2016) - He, Yumin; Gao, Yang; Zhang, Xiaolong; Dong, Yabin
Abstract: Lifted multiwavelet not only has the local analysis characteristics, and multi-scale, multi-resolution characteristics, but also has the flexibility property for constructing wavelet. It has shown a good prospect in solving singular problem, large gradient problem. This paper introduces lifted multiwavelet to FEM and constructs the elements based on lifted multiwavelet based on space lifting. Furthermore, the method is applied in fault diagnosis of pipe crack.